BMI and all-cause mortality in a population-based cohort in Rural South Africa - Manne-Goehler, Jennifer; Baisley, Kathy; Vandormael, Alain; Bärnighausen, Till; Tanser, Frank; Herbst, Kobus; Pillay, Deenan; Siedner, Mark J. (Obesity, 2020)
Objective This study evaluates the association between BMI and all-cause and cause-specific mortality in South Africa. Methods Prospective, population-based observational cohort data from rural South Africa were analyzed. BMI was measured in 2010. Demographic characteristics were recorded and deaths were verified with verbal autopsy interview. The InterVA-5 tool was used to assign causes of death. HIV testing was conducted annually. Cox proportional hazards models were fit to estimate the effect of BMI on all-cause and cause-specific mortality, accounting for the competing risk of death from other causes. Models were adjusted for sociodemographic characteristics and HIV status, and inverse probability weighting for survey nonparticipation was used. Results The cohort consisted of 9,728 individuals. In adjusted models, those with BMI of 25.0 to 29.9 kg/m2 or 30.0 to 34.9 kg/m2 had a lower hazard of death (adjusted hazard ratio: 0.80; 95% CI: 0.69-0.92 and adjusted hazard ratio: 0.75; 95% CI: 0.60-0.93, respectively) compared with those with BMI of 18.5 to 24.9 kg/m2. Conclusions Individuals in South Africa who meet clinically defined criteria for overweight or obesity had a lower risk of all-cause mortality than those with a normal BMI. These findings were stronger for women and communicable conditions.
Gesehen am 26.08.2024